Processos fermentativos em café arábica: quais suas influências na qualidade do café? - Costa, Gisele Xavier Ribeiro (2024)
Specialty coffees have gained popularity due to their unique and complex flavors, as well as the meticulous care taken throughout the entire production process– from the seed to the cup. The pursuit of specialty coffees reflects both the discerning palates of coffee enthusiasts and an appreciation for a meticulously managed production chain. The quality and sensory profile of coffee can be influenced by several factors, such as microbial composition, growing conditions and post-harvest processing methods. In this perspective, this dissertation is structured into 3 chapters, with chapter 1 corresponding to a bibliographic review article that presents the microbiota of fruits and soils from Arabica coffee cultivation. The study of the coffee microbiota is becoming increasingly relevant, as these microorganisms can act positively in the production of higher quality coffees, altering the sensorial characteristics of the drink. Furthermore, it is worth highlighting that the microbiota is diverse and changes according to the growing region, coffee variety, processing methods used and agricultural practices, in addition to sharing between soil and fruit microorganisms. Chapters 2 and 3 address the results obtained in anaerobic fermentation experiments conducted on Arabica coffees. Fermentation is a method used in the post-harvest stage with the aim of improving the sensorial quality of the drink, developing varied and complex sensorial nuances. However, successful fermentation, leading to positive results, requires meticulous monitoring. Therefore, the experiments aimed to evaluate the influence of controlling ambient temperature and adding yeast inoculum on the physicochemical characteristics, the production of functional metabolites and improving the quality of the coffee drink. Arabica coffees, cultivars Paraíso and Arara, were subjected to self-induced anaerobic fermentation, in solid and submerged states, with and without room temperature, with and without the addition of inoculant. As a result, temperature control and the addition of yeast inoculum enabled greater microbial activity during fermentation and coffee drinks presented higher scores on the sensory scale compared to unfermented coffee. Furthermore, they presented a rich range of sensory perceptions, including notes of caramel, chocolate, brown sugar, honey, chestnuts, fruity, alcoholic, whiskey, rum, wine, floral, spices.